Os bastidores da adoção: o luto do "esperado" filho biológico - Borba, Mariane Candida Lira (2015)
This work aimed to reflect on the biological son mourning as important underlying aspect to demands for adoption, when this occurs due to infertility. Was used to analyze women s testimonies recorded in the book Motherhood Interrupted . The book consists of 40 statements from women who experienced pregnancy loss, is organizing Maria Manuela Bridge and this book published by the Association Project Artemis. There was mourning present in infertility and how often one is not experienced. Noted the importance of studying this time of grief and loss, so that if the couple settle into the adoption process to be successful. The work was conceived and structured with four chapters. In the first chapter was presented the story of each of the women studied. In the second chapter we reflect on the desire to have a child and the feelings experienced by not being fertile and its implications. In the third chapter was about the time of grief experienced by women studied and the view of some authors on the subject. The fourth and final presented to the narcissistic wounds that come with infertility and as of the narcissistic restoration after conception and not like the way can often lead to adoption.